Education, Justice, and Discursive Agency: Toward an Educationally Responsive Discourse Ethics. Issue 6 (December 2016) - Martin, Christopher
Abstract: Jürgen Habermas argues that principles of justice should be decided through rational agreement as opposed to force or coercion. Christopher Martin argues in this essay that the success of such a project presupposes sufficiently developed capacities for discursive agency equally distributed within a diverse public sphere. This epistemic presupposition is not explicitly recognized in Habermas's current formulation of his theory and as such the theory implicitly excludes the interest that future citizens have in the development of their own capacities for competent deliberative engagement. Martin argues that this omission is serious enough that Habermas's principle of universalization (U) should be modified, and he articulates this modification in terms of a prohibition against "developmental coercion." Martin concludes by elaborating on the concept of developmental coercion, and he points to the implications of this addition to discourse ethics for the institutionalization of deliberative democracy.